Exploring the longitudinal association between interventions to support the transition to secondary school and child anxiety. (July 2016) - Neal, S.; Rice, F.; Ng-Knight, T.; Riglin, L.; Frederickson, N.
Abstract: School transition at around 11-years of age can be anxiety-provoking for children, particularly those with special educational needs (SEN). The present study adopted a longitudinal design to consider how existing transition strategies, categorized into cognitive, behavioral or systemic approaches, were associated with post-transition anxiety amongst 532 typically developing children and 89 children with SEN. Multiple regression analysis indicated that amongst typically developing pupils, systemic interventions were associated with lower school anxiety but not generalized anxiety, when controlling for prior anxiety. Results for children with SEN differed significantly, as illustrated by a Group × Intervention type interaction. Specifically, systemic strategies were associated with lower school anxiety amongst typically developing children and higher school anxiety amongst children with SEN. These findings highlight strategies that schools may find useful in supporting typically developing children over the transition period, whilst suggesting that children with SEN might need a more personalized approach.